The Influence of Capital Structure, Asset Growth, and Total Asset Turnover Against Return on Equity in Construction and Building Companies Listed in Bei 2016-2019 - Ayu Wulandari Narhendra (Jurnal Ekonomi, 2020)
This study aims to determine the effect simultaneously and partially of capital structure, asset growth and TATO on Return on Equity.Data analysis used multiple linier regression analysis with SPSS application. Population in this research is the company of construction and building listed on BEI from 2016-2019. The research sample technique used purposive sampling with the results of 9 companies and 36 samples. The results showed partially, the regression coefficient value of the capital structure was 2.515 with a significance value of 0.017, so the capital structure had a significant effect on Return on Equity. And the TATO regression coefficientvalue is 3,479 with a significance value of 0.001. Then TATO has a significant effect on Return on Equity, while the regression coefficient value of Asset Growth is -0.459 with a significance value of 0.649. SoAsset Growth has no significant effect on Return on Equity. For the research results simultaneously the significance value is 0.008, which means that Capital Structure, Asset Growth and TATO have an influence on Return on Equity.